2008
DOI: 10.1068/p5824
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile–Auditory Interactions are Post-Perceptual

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
2
14
0
2
Order By: Relevance
“…Perceptual studies also provide evidence for auditory-somatosensory interactions. For example, facilitative interactions between audition and touch have been observed using subjective techniques such as loudness matching ͑e.g., Schürmann et al, 2004;Gillmeister and Eimer, 2007;Yarrow et al, 2008͒ as well as objective measurements of detection and discrimination ͑e.g., Schnupp et al, 2005;Wilson et al, 2009;Yau et al, 2009;Ro et al, 2009͒. Other studies ͑Gescheider et al, 1969Gescheider, 1970͒, however, have reported inhibitory results for the detection of a tactile stimulus in the presence of a suprathreshold auditory tone.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual studies also provide evidence for auditory-somatosensory interactions. For example, facilitative interactions between audition and touch have been observed using subjective techniques such as loudness matching ͑e.g., Schürmann et al, 2004;Gillmeister and Eimer, 2007;Yarrow et al, 2008͒ as well as objective measurements of detection and discrimination ͑e.g., Schnupp et al, 2005;Wilson et al, 2009;Yau et al, 2009;Ro et al, 2009͒. Other studies ͑Gescheider et al, 1969Gescheider, 1970͒, however, have reported inhibitory results for the detection of a tactile stimulus in the presence of a suprathreshold auditory tone.…”
Section: Introductionmentioning
confidence: 99%
“…This basic paradigm has been adapted by others to explore, for instance, auditoryvibrotactile interactions (Yarrow et al, 2008) and auditory influences on contrast detection (Lippert et al, 2007). Jaekl and Soto-Faraco (2010), in particular, showed that audiovisual enhancement induced by multisensory integration is more effective when visual stimuli present features compatible with the magnocellular pathway.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the presence of vibration tended to increase the loudness of the auditory stimulus. It should be noted, however, that based on the results of other experiments, Yarrow et al ͑2008͒ attributed the increase in loudness to a bias effect, concluding that the tactile stimulus "does not affect auditory judgments in the same manner as a real tone." Finally, Gescheider et al ͑1974͒ observed that magnitude estimates of a tactile vibratory signal were increased in the presence of a simultaneous auditory tone.…”
Section: Introductionmentioning
confidence: 91%